Conversion of Carbon Dioxide to Ethanol by Electrochemical Synthesis Method Using Brass as A Cathode - Septian Ramadan; Riyanto Riyanto (EKSAKTA: Journal of Sciences and Data Analysis, 2017)
The effect of potential and gas flow rate were investigated to determine the optimum conditions of the electrochemical synthesis process to convert carbon dioxide to ethanol. The conversion process is carried out using a NaHCO3 electrolyte solution in an electrochemical reactor equipped with a cathode and anode. As cathode is used brass, while as anode is used carbon. The result of the electrochemical synthesis process was analyzed by gas chromatography to determine the content of the compounds produced qualitatively and quantitatively. The optimum electrochemical synthesis conditions to convert carbon dioxide to ethanol are potential and gas flow rate are 3 volts and 0.5 L/minutes with ethanol concentration yielded 1.32%.